Abnormal functional connectivity of habenula in untreated patients with first-episode major depressive disorder. (March 2020) - Wu, Zhou; Wang, Chun; Ma, Zijuan; Pang, Manlong; Wu, Yun; Zhang, Ning; Zhong, Yuan
Highlights: The first study to explore the differences of functional connectivity in the habenula between first-episode depressive patients and healthy controls. MDD patients developed increased habenular functional connectivity with regions of the dorsolateral prefrontal cortex. Aberrant functional connectivity of the habenula and dlPFC can distinguish MDD patients from the normal. Abstract: Major depressive disorder (MDD) is associated with abnormalities in emotional/cognitive processing and low reward sensitivity. The habenula has a pivotal role in these processes that may contribute to depression. However, there has been little research on the abnormal connectivity between the habenula and whole brain of first-onset MDD. We aimed to explore the differences of functional connectivity between patients and healthy controls using functional magnetic resonance imaging. We used seed-based resting-state fMRI to examine functional connectivity between the habenula and whole-brain in 49 first-episode depressive patients and 25 healthy controls. Compared to controls, patients with MDD demonstrated significant increases in functional connectivity between the habenula and the dorsolateral prefrontal cortex (dlPFC). Furthermore, the receiver operating characteristic (ROC) curve proved that connectivity between the habenula and dlPFC was highly predictive. Additionally, there was a positive correlation between Hamilton Rating Scale for Depression (HAMD) score and functional connectivity between the habenula and right dlPFC. We found that the aberrant functional connectivity to the habenula and dlPFC can distinguish MDD patients from the normal.